2013
DOI: 10.1115/1.4007894
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tip Leakage Vortex for Operating Range Enhancement of Centrifugal Compressor

Abstract: Recently, the application of turbochargers is increasing because they are effective in improving fuel consumption of engines. One of the most important turbocharger characteristics is compressor operating range, since it has been used in various driving patterns with the advent of variable geometry turbochargers. Owing to the complicated phenomena, such as rotating stall occurring at low flow rate condition, flow analysis is very difficult and details of flow structure have not been fully understood for a long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…Higher up in the mid frequency range, a second amplified broadband intensity is observed in between two times the RO and four times the RO frequency, in agreement with Tomita et al 11 as well as Evans and Ward 12 who designates this as the so-called whoosh noise. Whereas Raitor and Neise 7 relates this to tip clearance noise due to leakage between the shroud and the blade tips.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Higher up in the mid frequency range, a second amplified broadband intensity is observed in between two times the RO and four times the RO frequency, in agreement with Tomita et al 11 as well as Evans and Ward 12 who designates this as the so-called whoosh noise. Whereas Raitor and Neise 7 relates this to tip clearance noise due to leakage between the shroud and the blade tips.…”
Section: Discussionsupporting
confidence: 81%
“…Galindo et al 9 investigated the influence of the tip clearance size on the acoustic noise generation in a centrifugal compressor, where the variations of the tip clearance have been shown to have insignificant impact on the noise generation at nearsurge operating conditions. Other researchers (Mendonca et al 10 and Tomita et al 11 ) found the occurrence of the narrowband noise at higher frequencies with respect to the rotational speed. Mendonca et al 10 relates a rotating instability with this noise source.…”
Section: Introductionmentioning
confidence: 96%
“…Several researchers have focused on rotating stalls in axial compressors [1][2][3][4]. In addition, several studies have been devoted to the study of rotating stalls in centrifugal compressors [5][6][7][8]. In recent years, there has been a renewed interest in the leading edge vortex (LEV), which is shed from the leading edge of the blade and developing to a rotating stall.…”
Section: Introductionmentioning
confidence: 99%
“…The investigations to find the mechanisms of map width enhancement of OPT2 are beyond the scope of this paper. The authors have found out the breakdown of the tip leakage vortex plays an important role in stabilizing the unsteadiness of the flow near the stall condition in a separate study (14) .…”
Section: Cfd Resultsmentioning
confidence: 98%